The Use of Modern Information Technologies is a Necessary Means of Preventing the Conflicts of Legal Interests in the Judicial System of Russia - RYABTSEVA, E. V. (The journal of contemporary issues in business and government, 2021)
The scientific article studies the international and Russian experience of using information technologies to prevent conflicts of legal interests as one of the corruption risks in the judicial activity. The main directions of the development of the judicial system are theoretically substantiated to minimize corruption risks using technical advances. It is concluded that it is necessary to adopt a new version of the Concept of the information policy of the judicial system with clearly fixed legal guarantees for representatives of the judiciary against abuse by other persons, as a result of obtaining information about the activities of the court; a list of the authorities' powers of officials, ensuring control over the reliability and completeness of the information provided on the activities of the courts; the procedure for access, provision, and dissemination of information with the fixation of the requirements as to subjects that disseminate information about the activities of the courts.